2008
DOI: 10.1137/s0040585x97983213
|View full text |Cite
|
Sign up to set email alerts
|

On the Normal Approximation to Symmetric Binomial Distributions

Abstract: The optimal constant over square root of n error bound in the central limit theorem for distribution functions of sums of independent symmetric Bernoulli random variables is 1/ √ 2πn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…The first three moments of X i are equal to the first three moments of the standard normal distribution but the fourth moment differs, and so by Corollary 3.2 we have a n −1 bound for the quantity |Eh(W n ) − Φh| for h ∈ C 2 b (R). However, the Kolmogorov distance between W n , which is a standardised Binomial distribution, and Z is of order n −1/2 ; see Hipp and Mattner [12]. The n −1/2 rate is also optimal with respect to Wasserstein distance as can be seen as follows.…”
Section: )mentioning
confidence: 99%
“…The first three moments of X i are equal to the first three moments of the standard normal distribution but the fourth moment differs, and so by Corollary 3.2 we have a n −1 bound for the quantity |Eh(W n ) − Φh| for h ∈ C 2 b (R). However, the Kolmogorov distance between W n , which is a standardised Binomial distribution, and Z is of order n −1/2 ; see Hipp and Mattner [12]. The n −1/2 rate is also optimal with respect to Wasserstein distance as can be seen as follows.…”
Section: )mentioning
confidence: 99%
“…In 2007 C. Hipp and L. Mattner published an analytical proof of the inequality C 02 ≤ 1 √ 2π in the symmetric case [8]. In 2009 the second and third authors of the present paper have suggested the compound method in which a refinement of C.L.T.…”
Section: Introductionmentioning
confidence: 78%
“…Some words about bound (11). By (8), to get C 02 (N ) it is enough to calculate T (n) = sup p∈(0,0.5] T n (p) for every 1 ≤ n ≤ N , and then find max 1≤n≤N T (n). The calculation of T (n) is reduced to two problems.…”
Section: On Calculationsmentioning
confidence: 99%
“…I addressed Hipp and Chistyakov concerning the paper of Bentkus and Hipp and the sources of the proof of estimate (9). On July 18, 2011, Hipp answered that some results of the paper under inquiry were published in his joint work with Mattner [27] in 2007. In that paper it was demonstrated that…”
Section: Introductionmentioning
confidence: 99%
“…However, the problem of estimating the accuracy of the normal approximation for the case of arbitrary symmetric distribution of random summands was not considered in [27]. Chistyakov answered that during their meeting between 1996 and 2001 Bentkus "said rather categorically that inequality (11) was true, but he did not get around to publishing its proof."…”
Section: Introductionmentioning
confidence: 99%